KARAKTERISTIK EKSTRAK KULIT BUAH NAGA MERAH (Hylocereus Polyrhizus) DENGAN PENAMBAHAN BERBAGAI KOSENTRASI ASAM SITRAT SEBAGAI PEWARNA ALAMI MAKANAN - Addion Nizori; Nola Sihombing; Surhaini (Department of Agroindustrial Technology, Bogor Agricultural University, 2020)
Nowadays, the use of natural colorant and additives is very important for increasing consumer acceptability in processed foods. Anthocyanins are commonly used as natural colorants in the food industry. As unstable natural pigments they need protection. This study aimed to determine the characteristics of red dragon fruit peel extracts by adding various concetrations of citric acids as natural food colorants. Research design used was randomized complete design with six treatments, i.e. 0%, 2%, 4%, 6%, 8%, and 10% concentrations with four replicates. The results showed that varying citric acid concentration had a significant effect on pH, anthocyanin content, antioxidant activity and colour change. Increasing of citric acid was also observed which was correlated with colour lightness and anthocyanin content. The best results showed in addition of 2% citric acid concentration with pH value of 2.75, anthocyanin total content of 6,38 mg/50g, antioxidant activity value of 80,71% and colours values of L*, a*, and b* were 49, 59 and 14, respectively. Keywords: Anthocyanin, extraction, red dragon fruit peel, citric acid